(untitled) (Ibrahim Medical College Journal, 2016)
A cross sectional study was conducted in inpatient department of seven primary level hospitals care centers (PLHCs) and six tertiary level hospitals (TLHs) of the country. Total 2058 hospitalized patients were interviewed over a six month period from October 2012. Most of the patients (85.9% in TLH and 100% in PLH) were prescribed with antibiotics at the time of admission. Only 6.4% patients of TLHs treated with antibiotic had culture proven infection and rest of the patient of TLH and all the patients of PLH were treated with antibiotic empirically. Top prescribed antibiotic was ceftriaxone (39.64% in TLH, 59.64% in PLH). Parenteral route of antibiotic administration was preferred for both at TLHs and PLHCs (63.3% and 76.9%). The results of the present study indicated that antibiotics were widely and inappropriately used without following standard guidelines or based on any rationality. This is an alarming situation, and needs to be addressed by the relevant authority to save the people from growing antibiotic resistance. Ibrahim Med. Coll. J. 2015; 9(2): 42-44